A set of inherited dangerous disorders - Nature Research (16552612) (2015)
The incidence of a rare group of disorders called organic acidaemias may be high in Syria, but their prevalence is unclear due to a lack of diagnostic tests, according to new research published in the Qatar Medical Journal. Organic acidaemias (OA) are inherited disorders characterized by a defect in protein metabolism that causes amino acids and short chain fatty acids to accumulate within body fluids and tissues. They are rare disorders that are reported infrequently around the world. Although they are known to be more prevalent in the Arab world than elsewhere owing to high consanguinity rates, there is little information about them in Syria, where many cases are believed to go undiagnosed or misdiagnosed. Hala Khalil Shennar of Damascus University and her colleagues performed a retrospective cohort study to gather information about OA disorders in Syria and determine how they are diagnosed. Their study represents the first published data on the pattern of diagnosis and the clinical and demographic characteristics of Syrian OA patients. They recruited 134 patients referred to the metabolic unit at the Children's Hospital of Damascus between 2008 and 2012 and suspected to have OA disorders. Of these, 70 patients (or 52.2%) underwent biochemical testing to confirm the diagnosis. The vast majority of cases occurred in consanguineous marriages, and the disorders killed over a fifth of the children in the review the researchers performed. The researchers found that these patients had eight different OA disorders — the most common being methylmalonic acidaemia, of which there were 40 cases — and often presented with symptoms such as sleep apnea, respiratory distress, recurrent vomiting, and dehydration. This was also reported to be the most common disorder in other in many Arab countries such as Tunisia and Lebanon. OA disorders occur most frequently in newborns, and can be fatal if left undiagnosed. Importantly, the researchers noted that the diagnosis of the disease in Syria is often delayed, possibly due to the lack of a neonatal screening programme. This could mean some babies die before they are properly diagnosed. Shennar and her colleagues believe their findings suggest a higher incidence of OA disorders in Syria than previously thought. They stress, however, that it is difficult to extrapolate them to the wider Syrian population, and argue that further research is needed to better estimate their incidence and to determine the possibility and cost-effectiveness of applying a government mandatory newborn screening programme. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0